Features of physical rehabilitation of pregnant women after a new coronavirus infection COVID-19 - Maksimov I.L.; Grigorieva I.A.; Parfenova L.A. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to develop and experimentally evaluate the effectiveness of a method of physical rehabilitation of pregnant women who have suffered from Covid-19. Methods and structure of the study. A method of physical rehabilitation of pregnant women who have suffered from Covid-19 has been developed and experimentally tested, including a wide range of specially selected means and musical accompaniment. Results and conclusions. An analysis of the literature and regulatory sources showed that pregnant women who have had Covid-19 require special attention and rehabilitation. Rehabilitation should be individual, including physical education, massage, psychoprophylaxis and hardening. The experimental technique showed an improvement in the vital capacity of the lungs, muscle condition and joint mobility, and stabilization of the emotional state of the rehabilitators. The PR process for pregnant women who have had Covid-19 should be individual and include a wide range of non-drug methods (physical exercise, massage, psychoprophylaxis, hardening).